Proces Tadeusza Maja. Z dziejów oddziału AL „Świt” na Kielecczyźnie - Tokarska-Bakir, Joanna (Zagłada Żydów. Studia i Materiały, 2011)
Tadeusz Maj – one of the major commanding officers of the partisan units of the People’s Army (Armia Ludowa, AL) in Poland during World War II – was arrested in 1951. He was charged with murders on Jews in the forests near Iłża committed in the period from June/July 1944 to December that year. The victims of the People’s Army “Świt” detachment under Maj’s command were Jewish escapees from the labor camp in Starachowice, who decided to escape to the forest after they had found out that they would be deported to Birkenau at the end of June 1944. The article reconstructs the history of Tadeusz Maj’s trial and of other investigations on the murders on the Jews, which were never brought to an end. It documents the tensions at the turn of the 1940s and 1950s visible within the communist party apparatus, which was reluctant to investigate the truth about the Holocaust.